(untitled) (Journal of International Crisis and Risk Communication Research, 2021)
This article examines the position of victims and those affected within communication theory. Current research has broadly been skewed toward reputation management and protecting brand value as primary goals of crisis communication efforts. As crises affect real people, crisis communication theory needs to be adapted to include their needs. To assure their needs are met, an integration of business ethics and psychosocial mechanisms in the field of crisis communication is proposed. This integration prevents crisis communication output from becoming an additional source of stress to the affected in the aftermath of crises. We offer recommendations for crisis communication scholarship to be inclusive and beneficial to victims and the affected in the aftermath of crises.